One-year Results of a Factorial Randomized Trial of Aspirin versus Placebo and Clonidine versus Placebo in Patients Having Noncardiac Surgery. (April 2020) - Sessler, Daniel I.; Conen, David; Leslie, Kate; Yusuf, Salim; Popova, Ekaterina; Graham, Michelle; Kurz, Andrea; Villar, Juan Carlos; Mrkobrada, Marko; Sigamani, Alben; Biccard, Bruce M.; Meyhoff, Christian S.; et al.
Abstract : Background: The authors previously reported that perioperative aspirin and/or clonidine does not prevent a composite of death or myocardial infarction 30 days after noncardiac surgery. Moreover, aspirin increased the risk of major bleeding and clonidine caused hypotension and bradycardia. Whether these complications produce harm at 1 yr remains unknown. Methods: The authors randomized 10, 010 patients with or at risk of atherosclerosis and scheduled for noncardiac surgery in a 1:1:1:1 ratio to clonidine/aspirin, clonidine/aspirin placebo, clonidine placebo/aspirin, or clonidine placebo/aspirin placebo. Patients started taking aspirin or placebo just before surgery; those not previously taking aspirin continued daily for 30 days, and those taking aspirin previously continued for 7 days. Patients were also randomly assigned to receive clonidine or placebo just before surgery, with the study drug continued for 72 h. Results: Neither aspirin nor clonidine had a significant effect on the primary 1-yr outcome, a composite of death or nonfatal myocardial infarction, with a 1-yr hazard ratio for aspirin of 1.00 (95% CI, 0.89 to 1.12; P = 0.948; 586 patients [11.8%] vs. 589 patients [11.8%]) and a hazard ratio for clonidine of 1.07 (95% CI, 0.96 to 1.20; P = 0.218; 608 patients [12.1%] vs. 567 patients [11.3%]), with effect on death or nonfatal infarction. Reduction in death and nonfatal myocardial infarction from aspirin in patients who previously had percutaneous coronary intervention at 30 days persisted at 1 yr. Specifically, the hazard ratio was 0.58 (95% CI, 0.35 to 0.95) in those with previous percutaneous coronary intervention and 1.03 (95% CI, 0.91to 1.16) in those without (interaction P = 0.033). There was no significant effect of either drug on death, cardiovascular complications, cancer, or chronic incisional pain at 1 yr (all P > 0.1). Conclusions: Neither perioperative aspirin nor clonidine have significant long-term effects after noncardiac surgery. Perioperative aspirin in patients with previous percutaneous coronary intervention showed persistent benefit at 1 yr, a plausible sub-group effect. Abstract : This article reports 1-yr outcomes of the POISE-2 study. Consistent with the 30-day analysis, neither aspirin nor clonidine reduced a 1-yr composite of nonfatal myocardial infarction or death. In a subgroup analysis of patients who had prior percutaneous coronary interventions, those given aspirin had significantly fewer nonfatal myocardial infarctions and/or deaths.Supplemental Digital Content is available in the text.